Ethical issues in traditional herbal medical practice in Nigeria - Ezedike Edward; Chrisantus Kanayochukwu Ariche (International Journal of Humanities and Innovation (IJHI), 2019)
There is increased use and popularity of herbal medicine in Nigeria in recent times. Scholars from different fields have attributed this recent upsurge to economic issues, high cost of modern medical care, loss of confidence in synthetic drugs, resistant of diseases to some modern drugs and easy accessibility of herbal medicines and its practitioners, amongst others. According to the World Health Organization (WHO), a large portion of the world’s population patronizes traditional herbal medicines. However, there is perceived neglect of the core principles of health care ethics by the practitioners and marketers of traditional herbal medicine in Nigeria. This is worrisome. In this connection, this paper argues that Nigerians will benefit immensely from traditional herbal medicine if its practitioners and marketers observe and respect these core principles of health care which includes the principles of beneficence, nonmaleficence, autonomy, informed consent, justice, and truthfulness. This study is purely qualitative and adopts a textual critical analytic method.